2015
DOI: 10.1007/s00125-015-3628-2
|View full text |Cite
|
Sign up to set email alerts
|

Impact of high dose n-3 polyunsaturated fatty acid treatment on measures of microvascular function and vibration perception in non-alcoholic fatty liver disease: results from the randomised WELCOME trial

Abstract: The study was funded by the National Institute for Health Research UK and Diabetes UK.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…Patients with NAFDL and DM2 were supplemented using the same dosage of 4 g/day for 15–18 months of n-3 PUFAs and were evaluated on the threshold of vibration perception and microvascular cutaneous reactivity, which are indicators of early complications of DM2, insulin resistance, and obesity. The treatment resulted in a slight improvement in the threshold of vibration perception, but not associated with DM2 [ 191 ].…”
Section: Fatty Acidsmentioning
confidence: 99%
“…Patients with NAFDL and DM2 were supplemented using the same dosage of 4 g/day for 15–18 months of n-3 PUFAs and were evaluated on the threshold of vibration perception and microvascular cutaneous reactivity, which are indicators of early complications of DM2, insulin resistance, and obesity. The treatment resulted in a slight improvement in the threshold of vibration perception, but not associated with DM2 [ 191 ].…”
Section: Fatty Acidsmentioning
confidence: 99%
“…Besides sensory nerves, the second mechanism involves the epoxyeicosatrienoic acids, one of the main endothelium‐derived hyperpolarizing factors . Despite this physiological mechanism, oral supplementation with high doses of epoxyeicosatrienoic and docosahexaenoic acids does not improve PORH in patients with nonalcoholic fatty liver disease . A recent meta‐analysis showed an overall neutral effect of COX inhibition on skin PORH , suggesting no involvement of prostanoids.…”
Section: Which Dynamic Tests Are Commonly Used?mentioning
confidence: 99%
“…However, a recent meta-analysis of randomised controlled trials (RCTs) concluded that n-3PUFA supplementation has little effect on the prevention of T2D in humans [3], and evidence for preventing T1D remains preliminary and limited to animal studies [4]. In murine models, research has shown that increased n-3PUFA intake reduces the risk of microvascular complications in vivo [5], and some studies [6,7], although not all [8], have shown n-3PUFA supplementation improves biomarkers of vascular health and metabolic parameters in people with T2D [9,10]. However, RCTs investigating n-3PUFA supplementation in T2D have failed to show reductions in major vascular events [11].…”
Section: Introductionmentioning
confidence: 99%